Asiatic acid inhibits LPS-induced inflammatory response in endometrial epithelial cells. (March 2018) - Cao, Shou-yan; Wang, Wei; Nan, Fang-fang; Liu, Yan-ni; Wei, Shuang-yan; Li, Fang-fang; Chen, Li
Abstract: Accumulating evidence indicates that asiatic acid, a natural triterpene isolated from Centella asiatica, has anti-inflammatory activity. However, the anti-inflammatory effects of asiatic acid on LPS-stimulated endometrial epithelial cells and the involved molecular pathways have not been completely elucidated. In the present study, we evaluated the effects of asiatic acid on LPS-induced inflammatory response in endometrial epithelial cells. Mouse endometrial epithelial cells were treated with asiatic acid and stimulated with LPS. ELISA was performed to measure the levels of inflammatory cytokines TNF-α, IL-1β, and PGE2 . Western blot analysis was used to test the expression of PPARγ and NF-κB. The results showed that LPS-induced inflammatory mediators TNF-α, IL-1β, NO, and PGE2 were significantly inhibited by asiatic acid. Furthermore, LPS-induced TLR4 expression and NF-κB activation were concentration-dependently suppressed by asiatic acid. In addition, asiatic acid was found to increase the expression of PPARγ in a concentration-dependently manner. The inhibition of asiatic acid on inflammatory mediators production were prevented by PPARγ inhibitor, GW9662. Taken together, these results showed that asiatic acid exhibited its anti-inflammatory effects in endometrial epithelial cells by activating PPARγ. Highlights: LPS-induced inflammatory mediators TNF-α, IL-1β, NO, and PGE2 were significantly inhibited by asiatic acid. LPS-induced TLR4 expression and NF-κB activation were suppressed by asiatic acid. In addition, asiatic acid was found to increase the expression of PPARγ. The inhibition of asiatic acid on inflammatory mediators production were prevented by PPARγ inhibitor, GW9662.